2016
DOI: 10.1080/21691401.2016.1198365
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization and evaluation of mosquito-larvicidal property of silver nanoparticles synthesized from the seaweed, Turbinaria ornata (Turner) J. Agardh 1848

Abstract: The silver nanoparticles synthesized from Turbinaria ornata (To-AgNPs) showed spherical with crystalline nature (20-32 nm) was evaluated against fourth instar larvae of three mosquitoes. The maximum activity of To-AgNPs was recorded on Aedes aegypti followed by Anopheles stephensi and Culex quinquefasciatus with the following lethal concentration values (μg/ml): LC of 0.738, 1.134, and 1.494; and LC of 3.342, 17.982, and 22.475, respectively. The obtained respective values (μg/ml) vis-a-vis aqueous extract (To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 42 publications
6
17
0
Order By: Relevance
“…The presence of strong peaks of silver element around 3 KeV were observed, which indicate that the Ag is the major element in AgNPs, thus confirming the successful biosynthesis of AgNPs [28]. Similar peak (3 keV) has been reported by other researchers [29].…”
Section: Characterization Of Silver Nanoparticlessupporting
confidence: 87%
“…The presence of strong peaks of silver element around 3 KeV were observed, which indicate that the Ag is the major element in AgNPs, thus confirming the successful biosynthesis of AgNPs [28]. Similar peak (3 keV) has been reported by other researchers [29].…”
Section: Characterization Of Silver Nanoparticlessupporting
confidence: 87%
“…be attributed to electrons near each particle surface which become delocalized and are shared amongst neighbouring particles. In the case of samples A-B which were reduced by NaBH 4 , it was obvious that a similar trend with the absorbance maxima near 400 nm was obtained indicating a good agreement with Deepak et al 18 Absorbance spectra of samples D-G showed different trends. In the case of sample D, a shift of absorbance maximum to the shorter wavelength 351 nm is obvious while sample F shows a shift of absorbance maximum to the longer wavelength 423 nm.…”
Section: The Spectral Analysis Of Agnpssupporting
confidence: 85%
“…The antibacterial activities of the GA-AuNPs were evaluated by the agar well diffusion method [16]. Briefly, a series of sterile Nutrient agar media plates were swabbed with 100 μL of overnight bacterial cultures of Escherichia coli (MTCC 443), Serratia marcescens (MTCC 97), Klebsiella pneumonia (MTCC 432) and Bacillus subtilis (MTCC 441) Cultures respectfully.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…The seaweed extracts possesses bioactive metabolites like flavonoids, phenols, citric acid, ascorbic acid, polyphenolic, terpenes, alkaloids and reductase could act as reducing agents [14]. The earlier research suggest that there are some marine algae which are very good biological material for the synthesis of nanoparticles [15][16][17]. Interestingly we had done our study previously in Gelidiella acerosa for the first time, it has been reported that the synthesis of highly stable Ag-NPs, characterization and its antimicrobial activity [18].…”
Section: Introductionmentioning
confidence: 99%